Prevention of pressure ulcers among individuals cared for in the prone position: lessons for the COVID-19 emergency. (2nd June 2020) - Moore, Zena; Patton, Declan; Avsar, Pinar; McEvoy, Natalie L; Curley, Gerard; Budri, Aglecia; Nugent, Linda; Walsh, Simone; O'Connor, Tom
Abstract : Objective: Pressure ulcers (PUs) involve the destruction of skin and underlying tissue due to prolonged pressure and shear forces. These ulcers are painful and significantly reduce a person's quality of life. PUs are also expensive to manage and impact negatively on the achievement of cost-effective, efficient care delivery. Method: Prone positioning is a postural therapy that aims to enhance respiratory function through increasing oxygenation levels. In contemporary clinical practice, ventilation in the prone position is indicated for patients with severe acute respiratory distress syndrome. However, despite its advantages in terms of respiratory function, several studies have examined complications of prone position ventilation and have identified PUs (facial PUs as well as PUs on other weight-bearing areas of the body) as a frequent complication in patients who are already in a precarious medical situation. International data suggest that up to 57% of patients nursed in the prone position develop a PU. The aim of this clinical review is to identify and review evidence-based recommendations developed to facilitate the selection and application of preventive interventions aimed at reducing PU development in patients ventilated in the prone position. Given the current COVID-19 crisis, this review is timely as intensive care unit (ICU) patients with COVID-19 require ventilation in the prone position at a level that is disproportionate to the general intensive care population. Up to 28% of patients admitted to the ICU with confirmed infection due to severe COVID-19 are cared for in the prone position. The scope of this review is limited to adult individuals only. Results: The skin assessment should be undertaken before proning and following positioning the patient back into the supine position. Although it is essential to keep the skin clean and moisturised, using pH-balanced cleansers, there is inconsistency in terms of the evidence to support the type of moisturiser. Use of positioning devices in addition to repositioning is recommended to offload pressure points on the face and body. Further, using dressings such as hydrocolloids, transparent film and silicone may be of benefit in decreasing facial skin breakdown. Conclusion: Given the importance of PU prevention in this cohort of patients, adopting a focused prevention strategy, including skin assessment and care, offloading and pressure redistribution, and dressings for prevention may contribute to a reduction in the incidence and prevalence of these largely preventable wounds.